A fast screening approach for genetic tolerance to air pollution in Scots pine field tests - Danusevičius D; Marozas V; Augustaitis A; Plaušyte E (iForest - Biogeosciences and Forestry, 2013)
This study aims to develop a screening approach for genetic tolerance to industrial pollution in Scots pine. The relationship between temporal variation in strength of genetic control on radial increment of seed orchard clones affected by air pollution and past pollutant emissions from a nitrogen fertilizer plant in central Lithuania was assessed. The annual radial increment was measured from increment cores. High present-day defoliation was associated to low radial increment during intensive pollution period in the years 1992 - 1995 when high defoliation was recorded in the stands. There was a tendency for a stronger genetic control of radial increment during the years of high defoliation. The clones representing the extremes of high and low radial increments during the stress period of 1992 - 1995 were selected for further tolerance testing based on needle anatomy traits.